Pathological anatomy - de los Santos, Julio (Cirugía del Uruguay, 1973)
According to what is stated in the -classification already mentioned, we will deal with it. successively from: 1. Seminoma. two,. Teratomas: Differentiated. Intermediate malignant (types A and B). Anaplastic. Trophoblastic. 3. Combined tumor. Four . Rare tumors: interstitial cells. From Sértoli cells. Adenomatoid tumor.